2014
DOI: 10.3109/15563650.2014.885982
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of anonymised pooled urine from portable street urinals in central London identifies variation in the use of novel psychoactive substances

Abstract: This study demonstrates that analysis of anonymous pooled urine samples from stand-alone urinals can be used to detect and monitor trends in the use of classical recreational drugs and NPS in a large city centre over time. This technique has the potential to be a novel key indicator alongside other existing indicators to provide a more robust picture of the use of recreational drugs including NPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 10 publications
2
38
0
Order By: Relevance
“…DMAA was always considered to be prohibited by WADA, as a substance with a similar chemical structure or similar biological effect to listed stimulants. [21] Nevertheless, the study could not differentiate its presence as being part of an energy supplement or taken as an NPS. In the WADA Adverse Atypical Findings for 2009, methylhexaneamine (DMAA) was ranked joint third in the stimulant class.…”
Section: Introductionmentioning
confidence: 94%
“…DMAA was always considered to be prohibited by WADA, as a substance with a similar chemical structure or similar biological effect to listed stimulants. [21] Nevertheless, the study could not differentiate its presence as being part of an energy supplement or taken as an NPS. In the WADA Adverse Atypical Findings for 2009, methylhexaneamine (DMAA) was ranked joint third in the stimulant class.…”
Section: Introductionmentioning
confidence: 94%
“…However, DMAA has still been found in the general public. DMAA was detected in 25% urine samples collected from portable street urinals in central London [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…[59,66,67,69] Likewise, in studies evaluating substances found in seizures during legal investigations [72] or identifying substances found in the urinals in London, [73] MXE is regularly quoted. It is also regularly found, as are other new synthetic drugs, as a cutting agent in MDMA, amphetamine, ketamine or cocaine.…”
Section: Methoxetaminementioning
confidence: 99%